SOCIAL ENTREPRENEURSHIP MEWUJUDKAN KESEJAHTERAAN MASYARAKAT BERDASARKAN PRINSIP-PRINSIP EKONOMI SYARIAH - Mahmuda Mulia Muhammad (El-Iqthisadi, 2020)
Abstract               Studies on social entrepreneurship are still minimal compared to practice, of course it is a challenge for academics to deepen their studies on social entrepreneurship. In addition, social problems always arise and cannot be avoided at once and affect every aspect of people's lives. The purpose of this study is to examine social entrepreneurship in relation to Islamic economic principles in the welfare of society. This study uses a literature review which contains theories, findings and materials from previous studies as a basis for writing this article. The results of the study show that social entrepreneurship in Islamic economics is manifested by 3 fundamental principles in Islamic economics, namely tauhid (oneness), khilafah (representation) and 'is (fair). Social entrepreneurship is able to realize social welfare through reaching social problems and meeting community needs, avoiding social imbalances that are very far away, creating justice and maintaining environmental balance and avoiding elements of usury and clarity.Keywords: Community Welfare, Sharia Economic Principles, Social Entrepreneurship. AbstrakKajian tentang social entrepreneurship masih minim dibanding prakteknya, tentunya menjadi tantangan tersendiri bagi kalangan akademisi untuk memperdalam kajian-kajian mengenai social entrepreneurship. Selain itu, permasalahan sosial selalu timbul dan tidak dapat dihindari sekaligus serta mempengaruhi setiap aspek kehidupan masyarakat. Tujuan kajian ini untuk mengkaji tentang social entrepreneurship dalam kaitannya dengan prinsip-prinsip ekonomi syariah dalam memakmurkan masyarakat. Kajian ini menggunakan kajian literatur review yang berisi teori-teori, temuan dan bahan penelitian-penelitian terdahulu sebagai dasar dalam penulisan artikel ini. Hasil kajian menunjukkan bahwa social entrepreneurship dalam ekonomi syariah diwujudkan dengan 3 prinsip fundamental dalam ekonomi syariah yaitu tauhid (keesaan), khilafah (perwakilan) dan ‘adalah (adil). Social entrepreneurship mampu mewujudkan kesejahteraan masyarakat melalui menjangkau permasalahan sosial dan memenuhi kebutuhan masyarakat, menghindari adanya ketimpangan sosial yang sangat jauh, menciptakan keadilan dan menjaga keseimbangan lingkungan dan menghindari adanya unsur riba dan adanya kejelasan.Kata Kunci: Kesejahteraan Masyarakat, Prinsip Ekonomi Syariah, Social Entrepreneurship.